Analysis of biomechanics in athletes with disabilities: a systematic and narrative review - Lopes, J.; Guimarães, K. A.; Lopes, S. M.; Pérego, S. M.; Andrade, C. (Fisioterapia em Movimento, 2023)
Introduction Specifically in athletes with disabilities, investigations and biomechanical understanding seem to be even more relevant, as they provide data on how a certain type of disability limits sports practice and also describe parameters that allow the suggestion of relevant adaptations capable of guaranteeing a higher level comfort to practitioners.